Komunikasi Transparansi dan Akuntabilitas Polri dalam Penguatan Kepercayaan Publik: Studi Kasus Penanganan Pengaduan Masyarakat - Abim Sastrawan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Public trust in the Indonesian National Police (Polri) has fluctuated in recent years, particularly following several ethical violations and legal case-handling practices perceived as lacking transparency. This study examines government communication practices based on transparency and accountability in strengthening public trust in Polri, with a focus on the management of public complaints. Using a qualitative descriptive case study approach, the research analyzes secondary data from official Polri reports, public media, and relevant academic literature. The findings identify three key dimensions: transparency of public information through digital channels, communication responsiveness in handling complaints, and public accountability through performance reporting. Although the Dumas Presisi system has improved institutional openness and accountability, the communication practices remain largely semi-symmetrical and insufficiently participatory. Theoretically, this study extends the Two-Way Symmetrical Communication Theory by introducing the dimension of social empathy. Practically, it recommends strengthening Polri’s public communication to become more transparent, human-centered, and participatory in order to enhance institutional trust.